Estimating Poverty in a Fragile Context : The High Frequency Survey in South Sudan - Pape, Utz; Parisotto, Luca (World Bank, Washington, DC, 2019)
The High Frequency South Sudan Survey, implemented by the South Sudan National Bureau of Statistics in collaboration with the World Bank, conducted several waves of representative surveys across seven of the ten former states between 2015 and 2017. These surveys provided a long overdue update to poverty numbers in South Sudan, with the previous national poverty estimates dating as far back as 2009. The escalation and expansion of the civil conflict posed severe challenges to the planning and implementation of fieldwork. The surveys therefore capitalized on several technological and methodological innovations to establish a reliable system of data collection and obtain valid poverty estimates. Focusing on the 2016 urban-rural wave, this paper describes the design and analysis of the survey to arrive at reliable poverty estimates for South Sudan, utilizing the Rapid Consumption Methodology combined with geo-spatial data for inaccessible survey areas.